Desain Rangkaian AC to DC Full Wave Rectifier Menggunakan IC LM338T Untuk Mengatur Output Tegangan dan Arus - Aqmal, Faril (CV. Sekawan Siji, 2024)
This paper discusses the design of a full-wave-rectifier AC to DC circuit using the LM338T IC to regulate voltage, current and output based on load variations. Load variations cannot be regulated using DC current and cause the load to vary. Therefore, a modification of the full wave rectifier circuit with IC LM338T is proposed for regulation based on load variations. The results show that variations in motor load produce voltage, current and power of 1.25 Vdc each, an output current of 0.10 A, and an output power of 0.12 watts. Using the LM338T IC can regulate the output voltage from 1.25–32 Vdc and a current of 5 A. If the load exceeds 5 A, the voltage will decrease and the resulting wave rectifier will experience distortion. So that the performance of the IC lasts longer, add a heat-sink to dissipate heat.